2022
DOI: 10.2147/jir.s342830
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Features, Immune-Inflammatory Markers, and Outcomes Between Patients with Acute In-Hospital and Out-of-Hospital Ischemic Stroke

Abstract: We investigated the differences of clinical features, four immune-inflammatory markers, namely neutrophil counts, plateletto-lymphocyte ratio, neutrophil-to-lymphocyte ratio (NLR), and systemic immune-inflammation index (SII), as well as outcomes between patients with in-hospital ischemic stroke (IHIS) and out-of-hospital ischemic stroke (OHIS). Patients and Methods: We retrospectively enrolled 72 patients with IHIS and 3330 patients with OHIS. Results: IHIS accounted for 2% of all patients with ischemic strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…The present study also revealed elevation of serum RvD1 from admission to discharge in patients with AIS, likely due to the level of inflammation in patients with AIS being correspondingly ameliorated by in-hospital treatment ( 52 , 53 ). In addition, serum RvD1 is a widely endorsed anti-inflammatory factor, the elevation of which represents resolution of acute inflammation ( 54 ).…”
Section: Discussionsupporting
confidence: 61%
“…The present study also revealed elevation of serum RvD1 from admission to discharge in patients with AIS, likely due to the level of inflammation in patients with AIS being correspondingly ameliorated by in-hospital treatment ( 52 , 53 ). In addition, serum RvD1 is a widely endorsed anti-inflammatory factor, the elevation of which represents resolution of acute inflammation ( 54 ).…”
Section: Discussionsupporting
confidence: 61%
“…In studies that included diabetic and non-diabetic patients, SII greater than 2140 could predict poor outcomes in stroke patients after endovascular thrombectomy 34 . Also, SII greater than 2120 was an independent risk factor of mortality among patients with ischemic stroke in another study 35 . Different cut-off values that can predict outcomes among patients with ASCVD were described in two meta-analyses 14 , 17 .…”
Section: Discussionmentioning
confidence: 84%
“…A previous study based on the MIMIC-IV database showed that a high SII increased 30-day all-cause mortality ( 36 ). Chen investigated the difference between four inflammatory immune markers in predicting the outcome of patients with ischemic stroke ( 37 ). Moreover, in a meta-analysis, high SII was strongly associated with poor ischemic stroke outcomes and a high mortality rate ( 38 ).…”
Section: Discussionmentioning
confidence: 99%